2014
DOI: 10.7498/aps.63.094205
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emission from a two-level atom in a dynamic photonic crystal with an isotropic disoersion relation

Abstract: The spontaneous emission of a two-level atom, located in an isotropic photonic crystal with dynamically modulated photonic band edge, has been studied. When the photonic band edge is modulated with step functions or triangle functions, the evolution of atomic population on the upper level has been discussed. When the photonic band edge is modulated with step functions, the dynamics of atomic population depends not only on the detuning value of the atomic transition frequency from the band edge, but also on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recently, EIT shows the wide applications in the field of cavity optomechanics, [9] optical lattice for cold atoms, [10] and hybrid atom-molecular system. [11,12] Photonic crystal structure [13][14][15][16] with periodically varying refractive index is capable of controlling the flow of light wave. The main feature is to open photonic band gaps (PBGs) resulting from Bragg scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, EIT shows the wide applications in the field of cavity optomechanics, [9] optical lattice for cold atoms, [10] and hybrid atom-molecular system. [11,12] Photonic crystal structure [13][14][15][16] with periodically varying refractive index is capable of controlling the flow of light wave. The main feature is to open photonic band gaps (PBGs) resulting from Bragg scattering.…”
Section: Introductionmentioning
confidence: 99%
“…At present, three-component cropping system should be established instead of two-component cropping system by cropping structure adjustment. Studies had shown that "ryegrass-rice" rotation system not only produce a large number of high-quality forage, but also improve the paddy soil properties [6][7][8][9]. In this project, we interplanted L. perenne under the fruit trees, and determined its nutrient contents.…”
Section: Introductionmentioning
confidence: 99%